Influence of product market competition and managerial competency on corporate environmental responsibility: Evidence from the US. (1st July 2021) - Tsendsuren, Chuluunbat; Yadav, Prayag L.; Han, Seung Hun; Kim, Hohyun
Abstract: Previous findings on the relationship between corporate environmental responsibility and firm performance have not been conclusive or consistent; therefore, scholars have increasingly paid attention to the role of external factors that shape corporate environmental behavior. Among various potential factors, this study focused on product market competition and managerial competency. Specifically, we investigated the influence of product market competition on corporate environmental responsibility and firm performance, and further examined whether managerial competency moderated this influence. Using 2015–16 Newsweek's green rankings covering 500 of the largest publicly traded US firms, the regression results showed that product market competition tends to discourage firms from addressing environmental challenges. Importantly, however, managerial competency played a positive moderating role in enhancing corporate environmental practices under market competition. Moreover, while product market competition lowered profitability in general, firms with greater environmental efforts retained their profitability under strong competition, although this effect was only found for firms with competent managers. The findings exhibited robustness in several alternative methods, including lagged variables and instrumental variable approaches. This study identifies external factors that influence corporate environmental responsibility and extends the body of knowledge by capturing the moderating role of managerial competency. It also provides insights for policymakers and practitioners regarding environmental management. Strategic integration of corporate environmental responsibility in corporate functioning will pave the way for executing stakeholder sagacity in a competitive environment. Graphical abstract: Image 1